A multicenter phase II trial of paclitaxel, carboplatin, and cetuximab followed by chemoradiotherapy in patients with unresectable locally advanced squamous cell carcinoma of the head and neck. (13th January 2020) - Enokida, Tomohiro; Ogawa, Takenori; Homma, Akihiro; Okami, Kenji; Minami, Shujiro; Nakanome, Ayako; Shimizu, Yasushi; Maki, Daisuke; Ueda, Yuri; Fujisawa, Takao; Motegi, Atsushi; Ohkoshi, Akira; et al.
Abstract: Background: Induction chemotherapy (IC) in locally advanced squamous cell carcinoma of the head and neck (LA‐SCCHN) often compromises compliance with subsequent chemoradiotherapy (CRT), which negatively affects outcomes. Here, we assessed the combination of paclitaxel (PTX), carboplatin (CBDCA), and cetuximab (Cmab) as IC for unresectable LA‐SCCHN. Methods: Induction chemotherapy consisted of weekly CBDCA area under the plasma concentration‐time curve = 1.5, PTX 80 mg/m 2 and Cmab with an initial dose of 400 mg/m 2 followed by 250 mg/m 2 for 8 weeks. Following IC, CDDP (20 mg/m 2, 4 days × 3 cycles) and concurrent radiotherapy (70 Gy/35 fr) were started. Primary endpoint was the proportion of CRT completion (%CRT completion). PCE was planned to be deemed effective if the Bayesian posterior probability (PP), defined as the probability that %CRT completion was larger than the threshold value of 65%, exceeded 84%. Results: Thirty‐five patients were enrolled. Cases were hypopharynx/oropharynx/larynx in 17/17/1 patients, all at Stage IV. Of 35 patients, 34 (97%) completed IC and 32 received CRT and met the criteria of full analysis set (FAS). In FAS, the %CRT completion was 96.9%, and PP was 99.9%, exceeding the prespecified boundary of 84%. Mean cumulative dose and relative to dose intensity of CDDP in CRT was 232.5 mg/m 2 and 100%, respectively. Response rate was 88.6% by IC and 93.8% in the CRT phase. Three year overall survival was 83.5%. Main grade 3 toxicities included neutropenia (11.4%) and skin rash (5.7%) during IC; and oral mucositis (31.3%) and neutropenia (12.5%) during CRT. No grade 4 toxicity or treatment‐related death was seen. Conclusions: PCE as IC was feasible, with promising efficacy and no effect on compliance with subsequent CRT in unresectable LA‐SCCHN. Abstract : The combination of PCE as induction chemotherapy was feasible and had no effect on compliance with subsequent chemoradiotherapy (CRT) with CDDP, and provided encouraging efficacy in high‐risk unresectable locally advanced squamous cell carcinoma of the head and neck (LA‐SCCHN). The regimen is a favorable alternative to TPF for LA‐SCCHN patients who required more aggressive treatment, herein sequential CRT.